Larch tree carbon pools across a post-fire tree density gradient in far northeastern Siberia, 2010 - 2017 - Alexander, Heather; Paulson, Alison; Hewitt, Rebecca; Loranty, Michael; Mack, Michelle; Natali, Sue (NSF Arctic Data Center, 2021)
Fire severity is increasing in larch forests of the Siberian Arctic as climate warms, and initial fire impacts on tree demographic processes could be an especially important determinant of long-term forest structure and carbon (C) dynamics. We hypothesized that changes in post-fire larch recruitment impact C accumulation through tree density impacts on understory microclimate and permafrost thaw. We tested these hypotheses by quantifying C pools across a Cajander larch (Larix cajanderi Mayr.) tree density gradient within a fire perimeter near Cherskiy, Russia that burned in 1940. Across the density gradient, from 2010 - 2017 we inventoried larch trees and harvested ground-layer vegetation to estimate above ground contribution to C pools. We also quantified woody debris C pools and sampled below ground C pools (soil, fine roots, and coarse roots) in the organic + upper mineral soils. Our findings should highlight the potential for a climate-driven increase in fire severity to alter tree recruitment, successional dynamics, and C cycling in Siberian larch forests.